Fostering Critical Reflection in Primary Education through STEAM Approaches - Marcel Bassachs; Dolors Cañabate; Lluís Nogué; Teresa Serra; Remigijus Bubnys; Jordi Colomer (MDPI AG, 2020)
This paper describes a quantitative study that explores teaching practices in primary education to sustain the hypothesis that students' critical thinking may be activated through individual and group reflection. The study examines the quality of the reflections from primary school students during group processing when participating in Science, Technology, Engineering, Arts, and Math (STEAM) instructional approaches. The project's core methodology lies in scientific (physics) and artistic (dance) instructional activities which were executed in a continuous reflective and cooperative learning environment. The educational approach was refined by analyzing the reflective discussions from focus groups where descriptive, argumentative, reflective and critical reflective knowledge about acquired knowledge, competences, beliefs, attitudes and emotions were considered. While the educational intervention proved that 1st-year (K-7) students essentially reflected at the level of description, 3rd-year (K-9) and 5th-year (K-11) students, however, attained higher levels of individual critical reflection development than initially anticipated. The STEAM approaches were found to produce significant use and understanding of both science and artistic concepts and to increase a sense of competence readiness and a perception of modes of cooperation such as individual responsibility and promotive interaction.